[Rezension von: Byrne, Brendan, 1939-, Paul and the economy of salvation : Reading from the Perspective of the Last Judgment] - Moloney, Francis J. (The Australasian Catholic record, 2022)
Review(s) of: Paul and the economy of salvation: Reading from the perspective of the last judgment, by Brendan Byrne, (Grand Rapids, MI: Baker Academic, 2021), pp. xvi + 286, hardback, $54.99.